The Relationship of Knowledge Level and Mother's Fear on the Side Effects of IUD Contraception at Sipatana Health Center - Zaliha Almaira Bobihoe; Ridha Hafid; Mihrawaty S. Antu (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Intra Uterine Device (IUD) is an effective long-term contraceptive method, but users are still low. The use of IUD contraceptives is only about 19–20%. Barriers to IUD use include fear of side effects, lack of information, and myths that develop in society. This study aims to determine the relationship between knowledge level and mother's fear of the side effects of IUD contraception in the working area of the Sipatana Health Center. The study used a quantitative method with an analytical observational study design, using a cross sectional approach. The population of this study is mothers who use non-IUD contraceptives totaling 1,567 people. The sample amounted to 93 respondents using the purposive sampling technique. The research instrument uses knowledge and mother's fear instruments. Data analysis using the Chi-Square test. The results showed that there was a relationship between the level of knowledge and mother's fear, obtained p-value = 0.000 which was smaller than the significance value of ? = 0.05 which means that the lower the mother's knowledge, the higher the fear. This research is expected to be an evaluation material related to the use of IUDs in the work area of the Sipatana Health Center as well as an initial screening related to mothers' fears of IUD use